2024
DOI: 10.1186/s41938-024-00771-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the efficacy of a Trichoderma asperellum-based seed treatment for controlling Fusarium equiseti in chickpea

Manal Adnani,
Naila El Hazzat,
Soukaina Msairi
et al.

Abstract: Background Chickpea plant (Cicer arietinum L.) is an important legume crop that is vulnerable to various fungal pathogens causing significant yield losses. Among them, Fusarium equiseti is a pathogen that has started to raise concern. In contrast, Trichoderma species have been explored for their ability to control such pathogens. In this study, the efficacy of a novel seed treatment formulation was explored for controlling F. equiseti in chickpea plants. The formulation was designated to enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Although it appeared infrequently (2%) in our study, it has been documented in chickpeas from different global regions. Recent research in Canada, Morocco, and Iran has demonstrated that this species causes wilt and root rot in chickpeas [18,55,56]. The presence of F. equiseti in multiple geographic areas underscores its potential significance in chickpea pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it appeared infrequently (2%) in our study, it has been documented in chickpeas from different global regions. Recent research in Canada, Morocco, and Iran has demonstrated that this species causes wilt and root rot in chickpeas [18,55,56]. The presence of F. equiseti in multiple geographic areas underscores its potential significance in chickpea pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Given that F. avenaceum has a broad host range and can infect small grain crops such as barley, wheat, and canola [19,40], alternative non-host crops for this aggressive species must be incorporated into crop rotation programs. Previous studies [50][51][52][53][54][55][56][57][58][59][60][61][62] highlighted the need for identifying sources of resistance to F. oxysporum f. sp. ciceri.…”
Section: Discussionmentioning
confidence: 99%